Gerakan Affirmasi Untuk Kesetaraan: Kuota 30%, Peran DPIA dan Representasi Perempuan Aceh di Parlemen - Tri Fitriani Puspitasari (Jurnal Kebijakan Pembangunan, 2018)
This paper discusses the Affirmation Movement conducted by Aceh women in improving their representation in Parliament. Women now have a more open opportunity to engage in policy-making, especially with regard to budgeting and women's empowerment in politics. The purpose of this paper is to identify three things, first, it is necessary to have a strong female character to win female candidates in legislative elections in Aceh. Second, that there is a significant difference between Deliberative democracy initiated by Habermas and the Acehnese women's movement. Third, look at any movements carried out by the DPIA to win female candidates. The method used is the explanatory Qualitative method and using Participatory Action Research (PAR) for data collection method, where researchers are directly involved in several movement agendas.There are numerous social organizations that grew up after the Helsinki negotiations focusing on women's empowerment. The organizations then formed a network called Inong Aceh Inshore Center and held the Great Congress of Aceh Women named DPIA (Duek Pakat Inong Aceh). One of the DPIA's agenda is to win women candidates in legislative and political education elections. The main question of this paper is "What is the strategy of Aceh women in doing affirmative movement to improve women representation in parliament? And why is that strategy necessary? To answer these two questions, the author uses the Theory of Liberal Feminism and Deliberative Democracy Theory. The two theories found that there is a difference between Liberal Feminism through women's Affirmation movement in America and Australia Affirmation with Afrirmative movement in Aceh. In Aceh, women are faced with a very strong religious dogma, religious dogmas like strictly prohibited women lead this also affects the solidity of the Acehnese women's movement. In the theory of Deliberative Democracy, dialogue is carried out by interest groups to government actors, it turns out that in Aceh Women's Movement the interest groups that propose to the government are also purely governmental actors. This paper also discusses the shift of women movement after DPIA III, the shift of women movement then adjusts to social condition of Aceh society today. Religious dogma is still a barrier, and used by a group of people to bring down women candidates who go forward as leaders. The recommendations proposed to women's groups are to provide political education for women and the regeneration of women's primary leadership in the DPIA. Abstrak Tulisan ini membahas tentang GerakanAffirmasi yang dilakukan oleh perempuanAceh dalam meningkatkan keterwakilanperempuan di Parlemen. Saat ini perempuan memiliki kesempatan yang lebih terbuka untuk terlibat di alam pembuatan kebijakan, terutama yang berkaitan dengan budgeting dan pemberdayaan perempuan dalam politik. Tujuan dari tulisan ini adalah untuk mengetahui dua hal pertama, perlu ketokohan perempuan yang kuat untuk memenangkan kandidat pere mpuan pada pemilu legislatif di Aceh. Kedua,bahwa ada perbedaan yang signifikan antara demokrasi Deliberatif yang digagas oleh Habermas dengan pergerakan perempuan Aceh. Ketiga, melihat gerakan apa saja yang dilakukan oleh DPIA untuk memenangkan kandidat perempuan. Metode yang digunakan adalah metode Kualitatif eksplanatif dengan pengumpulan data menggunakan Participatory Action Research ( yakni peneliti terlibat langsungdalam beberapa agenda gerakan. Banyak sekali organisa si organisasi sosial yang tumbuh pasca perundingan Helsinki yang memfokuskan diri dalam pemberdayaan perempuan. Organisasi organisasi tersebut kemudian membentuk jaringan dalam sebuah wadah Balai Syura Inong Aceh dan mengadakan Kongres Besar Perempuan Aceh bernama DPIA Duek Pakat Inong Aceh Salah satu agenda DPIAini adalah memenangkan kandidat perempuan dalam pemilu legislatif dan pendidikan politik. Pertanyaan pokok tulisan ini adalah “Bagaimanastrategi perempuan Aceh dalam melakukan ge rakan affirmasi untuk meningkatkan keterwakilan perempuan di perlemen? dan mengapa strategi tersebut diperlukan? Untuk menjawab dua pertanyaan ini, penulis menggunakan Teori Feminisme Liberal dan Teori Demokrasi Deliberatif. Dengan dua teori tersebut ditemukan bahwa ada perbedaan antara Feminisme Liberal melalui gerakan Affirmasi perempuandi Amerika dan Australia Affirmasi dengan gerakan Affirmasi di Aceh. Di Aceh, perempuan dihadapkan pada dogma agama yang sangat kuat, dogma agama seperti perempuan haram memimpin ini juga mempengaruhi soliditas gerakan perempuan Aceh. Pada teori Demokrasi Deliberatif, dialog dilakukan oleh kelompok kepentingan kepada aktor pemerintah, ternyata dalam Gerakan perempuan Aceh kelompokkepenti ngan yang memberikan usulan kepada pemerintah adalah juga murni aktor pemerintah. Tulisan ini juga membahas tentang pergeseran gerakan perempuan setelah DPIA III, pergeseran gerakan perempuan kemudian menyesuaikan dengan kondisi sosial masyarakat Aceh saat ini. Dogma agama masih jadi batu sandungan, dan dimanfaatkan oleh sekelompok orang untuk menjatuhkan kandidat perempuan yang maju sebagai pemimpin. Rekomendasi yang diajukan kepada kelompok perempuan adalah dengan memberikan pendidikan politik bagi peremp uan dan regenerasi kepemimpinan perempuan utamanya dalam DPIA.